Do Personal Benefits, Professional Commitment, and Ethical Orientation Influence Earnings Management - Lasdi, Lodovicus (The Indonesian Journal of Accounting Research, 2025)
Financial reports are a means for companies to communicate financial information to interested parties. The information in financial statements is generally used by external parties, investors, and creditors to make investment and lending decisions. The existence of stakeholders in these financial statements is likely to give rise to conflicts of interest, with each party seeking to maximise the benefits it can obtain, such as shareholders seeking a return on the share capital they have invested and managers seeking to be able to earn bonuses from the results of their performance. Shareholders' demands for stock returns may encourage managers to engage in earnings management. The research design used is a 2x2x2 full factorial experimental design, which aims to test and provide empirical evidence on the effect of personal gain, professional commitment, and ethical orientation on earnings management. A total of 146 students from several universities in Indonesia who were enrolled in or had passed the Accounting Theory course participated. Earnings management is measured by manipulating scenarios, and participants are asked to respond by completing a semantic differential scale related to the treatment given. This experimental research was conducted by randomly distributing questionnaires online through Google Forms, entering several classes through Zoom, and distributing them through personal chat. The test used in this study is ANOVA, and the study results indicate that personal gain and ethical orientation significantly affect profit management. In contrast to the professional commitment variable, the results showed no significant effect of professional commitment on earnings management.